PERSEPSI KONSUMEN TERHADAP CITRA MEREK KENTUCKY FRIED CHICKEN DI KECAMATAN MEDAN JOHOR - Murniyanti, Sri; Wibowo, Muhammad Rizaldy; Rukmini, Rukmini (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
This study aims to find out consumer perception of Kentucky Fried Chicken Brand Image in Medan District Johor. In this study, the authors used descriptive quantitative analysis with a sample of 80 consumers. This study was conducted by distributing questionnaires to Kentucky Fried Chicken consumers in Medan District Johor, to find out the results of the author's study using product moment correlation formula, simple regression analysis, validity test, reliability test, T test and determination test. From the results of the research conducted, it can be known that consumer perception has a positive and significant impact on brand image. Simple linear regression yield Y = 10,602 + 0.623 X+ e. The calculated t value for the consumer perception variable (X) is 20,543 when compared to the table t value of 1,664. So t calculated obtained greater than the value of table t or 20,543 >1,664, then it was also seen that the value of sig is less than the probability value of 0.05 or 0.000 < 0.05 then the consumer perception variable (X) has a contribution to the brand image (Y). The value of R indicates a simple correlation, namely consumer perception is 0.919 or 91.9%. It means the bigger the R means the closer the relationship.